2015
DOI: 10.2147/cia.s70372
|View full text |Cite
|
Sign up to set email alerts
|

A medical costs study of older patients with acute myocardial infarction and metabolic syndrome in hospital

Abstract: BackgroundOlder patients with acute myocardial infarction (AMI) usually have a poor prognosis, but whether this poor prognosis leads to high hospital costs remains unclear. This study investigated the clinical outcomes of and costs incurred by older patients with AMI and metabolic syndrome (MS) in hospital.Methods and resultsPatients with AMI seen at Qilu Hospital of Shandong University between January 2011 and May 2013 were separated into four groups: young non-MS patients (n=282), older non-MS patients (n=32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In our study, the length of stay was not significantly different between the two age groups, although other studies have shown that older patients with ACS had longer hospital stays. 30 , 31 Besides, in-hospital mortality was 7.4% among older patients and 0.9% among younger patients. Patients who were discharged from the hospital were followed by general cardiologists in an outpatient setting after an average of one month and then every year.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, the length of stay was not significantly different between the two age groups, although other studies have shown that older patients with ACS had longer hospital stays. 30 , 31 Besides, in-hospital mortality was 7.4% among older patients and 0.9% among younger patients. Patients who were discharged from the hospital were followed by general cardiologists in an outpatient setting after an average of one month and then every year.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, the length of stay was not significantly different between the two age groups, although other studies have shown that older patients with ACS had longer hospital stays. 30,31 Besides, in-hospital mortality was 7.4% among older patients and 0.9% among younger patients.…”
Section: Dovepressmentioning
confidence: 99%
“…Similarly, in a study conducted in Italy, which followed up patients for 12 months’ post-hospitalization for ACS, patients who died of a cardiovascular event had an average cost of around €16,000 compared with an average cost of around €11,000 for the entire ACS cohort [ 8 ]. In China, a small study in a single hospital in Shandong found that increased age was associated with increased treatment costs and poorer clinical outcomes [ 9 ]. In a study in the US of over 12,000 patients with ACS, which compared those with and without diabetes, the presence of diabetes was reported to incur significant additional hospitalization costs of $32,577 versus no diabetes $29,150 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“… 12 . On the other hand, Fan and colleagues and Kanitz and colleagues have shown in their studies longer hospital stays in older patients with ACS 25 , 26 .…”
Section: Discussionmentioning
confidence: 91%